Attitudes towards euthanasia and physician-assisted suicide among physicians and patients in a multi-cultural society of Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Shahar, Mohamed Arif; Ab Rahman, Jamalludin; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Mohd Shah, Azarisman Shah (2013)
Due to globalization and changes in the health care delivery system, there has been a gradual change in the attitude of the medical community as well as the lay public towards greater acceptance of euthanasia as an option for terminally ill and dying patients. Physicians in developing countries come acros situations where such issues are raised with increasing frequency. As euthanasia has gained worldwide prominence, we aim to explore the beliefs and attitude of our patients and physicians towards it and related issues.